Evaluation and Comparison of the Position of the Apical Constriction in Single-root and Multiple-root Teeth - Alireza Farhad; Seyed Amir Mousavi; Shirin Shahnaseri; Pedram Iranmanesh; Javad Kafashi (Mashhad University of Medical Sciences, 2017)
Introduction: Precise knowledge of the location of the apical constriction is essential to root canal treatment and long-term prognosis. Considering the differences in the apical constriction and size of the roots in single- and multiple-root teeth in various races, examination and comparison of the location of the apical constriction in single-root and multiple-root teeth are of paramount importance. The present studies aimed to measure and compare the distance of the apical constriction from the apical foramen and anatomical apex in single-root and multiple-root teeth. Materials and Methods: In this cross-sectional study, 60 roots of single-rooted teeth and 60 roots of multiple-rooted teeth were collected from the patients referring to the health centers in Isfahan, Iran. After cleansing and disinfecting the surface of the roots, the surface of the teeth was washed with hypochlorite. Based on the direction of the apical foramen, a longitudinal cut was made in the same direction, and the roots were examined microscopically at the magnification of 25. Following that, the distance of the apical constriction from the apical foramen and anatomical apex was measured using a digital camera. In addition, mean and standard deviation of the obtained distance values were determined. Distances in the single-root and multiple-root teeth were compared using independent t-test, at the significance level of Results: Mean distance between the apical constriction and apical foramen was 0.86±0.33 mm in the single-root teeth and 0.072±0.27 mm in the multiple-root teeth. Mean distance between the apical constriction and anatomical apex was 1.14±0.36 mm in the single-root teeth and 1.03±0.36 mm in the multiple-root teeth. Moreover, the results of independent t-test showed the distance of the apical constriction from the apical foramen to be significant between single-root and multiple-rooted teeth (P=0.013). However, the distance between the apical constriction and anatomical apex was not considered significant in single-root and multiple-root teeth (P=0.095). Conclusion: According to the results, the termination of root canal treatment should be 0.86 and 0.024 mm shorter than the apical foramen, while it should be 1.14 and 1.03 mm shorter than the anatomical apex in single-root and multiple-root teeth, respectively.